PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT MAYORA INDAH TBK PERIODE 2014-2023 - Fito Ahmad Rizki; Ananda Hadistia (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of capital structure and profitability on firm value at PT Mayora Indah Tbk during the 2014–2023 period. The study employs a quantitative approach using secondary data obtained from the company’s annual financial statements over ten years. The independent variables are capital structure proxied by Debt to Equity Ratio (DER) and profitability proxied by Return on Assets (ROA), while firm value is measured using Price to Book Value (PBV). Data analysis was conducted using multiple linear regression with SPSS version 26, including classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results indicate that DER has a significant effect on firm value, while ROA does not have a significant effect individually. However, simultaneously, DER and ROA significantly affect firm value. The coefficient of determination of 57.8% suggests that firm value variations are largely explained by capital structure and profitability.